The Use of Metaphors and Tragic Pictures in Eugene O’Neill‘S American Drama - Al-Selman Selman, Haider; Zainal, Zaidah (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to explore the use of metaphors in Eugene O’Neil’s plays, particularly in depicting the tragic images of the plays. It is observed that there are some links on the use of metaphors to illustrate some heartbreaking scenes and acts. In this paper, tragic pictures include death, murder, and sadness in the craftsman of the plays, while the metaphorical expressions include simile, personification. The researcher intends to show how the tragic images are portrayed by the metaphorical expressions employed in the plays.
Keywords: Blackness; Desires; Eugene O’Neill; Metaphor; Suffering; Tragic.